2018
DOI: 10.1111/xen.12460
|View full text |Cite
|
Sign up to set email alerts
|

Ascites formation accompanied by portal vein thrombosis after porcine islet xenotransplantation via the portal vein in Rhesus macaque (Macaca mulatta)

Abstract: Pig-to-nonhuman primate (NHP) islet transplantation has been widely conducted as a preclinical xenotransplantation model prior to human clinical trial. Portal vein thrombosis is one of the complications associated with islet infusion through the portal vein into the liver. Here, we briefly report severe case of ascites formation accompanied by portal vein thrombi after pig-to-NHP islet xenotransplantation in a rhesus monkey. Meticulous prophylactic treatment such as continuous heparin infusion should be implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, we demonstrated that MMC preconditioning significantly suppressed the expression of IL-1β, MCP-1, IL-6 and TNF-α in islet allografts. Previous reports demonstrated a unique immunomodulatory approach to targeting proinflammatory cytokines such as IL-1β 26 , TNF-α 27 , MCP-1 28 and IL-6 29 , 30 and their respective receptors, and reported that the blockade of even one proinflammatory cytokine could prolong the survival of the transplanted islets. Our data, however, indicated that MMC preconditioning could induce the suppression of multiple cytokines, which was associated with poor outcomes 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we demonstrated that MMC preconditioning significantly suppressed the expression of IL-1β, MCP-1, IL-6 and TNF-α in islet allografts. Previous reports demonstrated a unique immunomodulatory approach to targeting proinflammatory cytokines such as IL-1β 26 , TNF-α 27 , MCP-1 28 and IL-6 29 , 30 and their respective receptors, and reported that the blockade of even one proinflammatory cytokine could prolong the survival of the transplanted islets. Our data, however, indicated that MMC preconditioning could induce the suppression of multiple cytokines, which was associated with poor outcomes 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternative site for the implantation of islets takes into consideration several factors such as the availability of oxygen, nutrients, and interaction with host immunity. As an alternative to portal vein infusion or kidney capsule implantation, Kim et al apply the use of a polymer scaffold interlayed with mesenchymal stem cells that modulate immune responses . The stem cells were also conditioned to survive in a low oxygen, hypoxic, and environment.…”
Section: Islet Transplantationmentioning
confidence: 99%
“…Descemet's membrane endothelial keratoplasty (DMEK) is an innovative transplantation technique that benefits from low rejection rates and requisite immunosuppression and results in superior vision recovery compared to other surgical techniques. Indeed, in current issue, Kim et al demonstrate that immunosuppression with the common agent tacrolimus can lead to asymptomatic thrombotic microangiopathy that can lead to a number of problems including organ damage. Minimizing the need for immunosuppression by improved graft quality, genetics, and preparation may therefore enhance tissue survival long term.…”
Section: Immune Suppressionmentioning
confidence: 99%